Serviços ecossistêmicos e produção animal no bioma Pampa: uma análise na área de proteção ambiental do Ibirapuitã - Vargas, Letícia Paludo (2017)
The diverses transformations that have been ocurring in ecosystems, and the search for strategies in order to attempt to achieve an environmentally sustainable and economically viable production system are becoming increasingly complex. Concerning the importance of the theme, this thesis aims to address the beef cattle production system, with regard to ecosystem services, in order to emphasize the case of the Associação de Produtores do Rincão do Vinte e Oito. Respecting this, two issues emerge as research problems: How does animal production in natural grasslands interfere on the sustainability of ecosystems? And how are ecosystem services embedded in productive and economic dynamics of rural producers? The main objective of the thesis is to analyze the ecosystem services provided by beef cattle and sheep farming in the natural grasslands, as regards to the producers of Área de Proteção Ambiental (APA) do Ibirapuitã. The database of the Projeto Aglomerados Urbanos em Áreas Protegidas (Urb-al Pampa) was used as unit of analysis, as well as a case study with farmers of the Association. As result, it became evident that the continuity of the associations in the animal production ocurrs particularly due to the traditionalism, since, economically, many farmers earn the greatest percentage of income from the retirement. In terms of ecosystem services, it can be observed that producers do not have a proper understanding of how the maintenance of production systems might generate benefits, although it is clear that a number of regulatory, provisioning and cultural services are present. The maintenance of livestock production is considered valid by the farmers as they believe that they can provide well-being for their families and the rest of the population. However, despite believing that they should receive some sort of benefit by preserving the natural grassland, they do not have a clear understanding of how to receive such remuneration, i.e., in case of Payment for Environmental Services (PES). Regarding PES policies, it is understood that the issue should be addressed more broadly with the farmers prior to the development of a conservation payment program. Thus, further studies are needed in order to properly assess the possibility of implementing PSA measures.